Diagnostic accuracy of CRP in the drainage fluid for early detection of anastomotic leakage in colorectal surgery – a pilot study - Ilektra Kyrochristou; Georgios Anagnostopoulos; Konstantina Psalla; Panagiotis Giannakakis; Athanasios Rogdakis (Folia Medica)
Introduction: Anastomotic leak (AL) in colorectal surgery remains a source of concern, as it jeopardizes patient recovery and increases morbidity, particularly if not detected early. The CRP in the drain fluid has barely been investigated as a new predictive marker of AL that would improve treatment outcomes. Materials and methods: A prospective pilot study conducted in our department included patients undergoing emergency colorectal surgery and primary anastomosis for benign and malignant disease. The CRP values of the drainage fluids and serum were measured on postoperative day 3 (POD3). The preoperative levels of albumin were also measured. Patients were followed for 2 months after their surgery, for the presence of clinical or subclinical AL. The accuracy of the CRP in the drain on POD3 to predict the incidence of AL was investigated. Secondary outcomes included the relation of the drain’s CRP to that of the serum and the incidence of AL in patients with low preoperative albumin levels. Results: Of the 188 patients who were treated for malignant and benign diseases of the small and large bowel, 56 were included in the study, 12 of whom were found to have an anastomotic leak. The estimated average C-reactive protein (CRP) level in drain fluid on postoperative day 3 (POD3) was significantly higher in the anastomotic leak (AL) group (t-test, t=−6.969, p<0.001). After examining the ROC curves, we defined a cut-off value for drain CRP of 77.65 mg/dL. This value demonstrated 91.7% sensitivity and 90.9% specificity in predicting AL. Furthermore, the odds of AL increased by 10.9% (95% CI [4.4%, 17.7%]) with each additional unit of CRP measured in the drain fluid. Conclusions: Maintaining a simple and cheap-to-measure prognostic factor of AL would be valuable in diminishing the devastating results of delayed leak identification. The CRP in the drain fluid seems a significant prognostic marker. We hope that the inclusion of more patients will confirm our results and highlight their significance.